Strategic Landscape in Higher Education: A Decadal Bibliometric Analysis of Competitive Dynamics (2013-2023) - Riske Faldesiani; Agus Rahayu; Heny Hendrayati (Jurnal Pendidikan Manajemen Perkantoran, 2024)
This study aims to review the literature on competitive dynamics in Higher Education Institutions (HEIs). The method used in this study is the PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) through a bibliometric approach with computational mapping analysis using VOS Viewer. The study period used as literature data material is articles and conference papers indexed in Scopus from 2013 to 2023. The keywords used were "higher education institution" and "competition". Of the 347 references deemed relevant, data reduction was performed with inclusion and exclusion criteria. The 10 articles with the highest number of citations were analyzed. The results of this study provide an overview for further research related to higher education strategies in facing competitive dynamics.